True or false?: prehistoric people. (Chicago, Illinois: Worldbook, 2019)
Did prehistoric people hunt dinosaurs? Did Stone Age people like to "rock out" to music? Do Neandertals live among us today? World Book's True or False?: Prehistoric People is here with the answers to these questions and more! The True or False? series reveals the surprising truths behind common misconceptions and teaches the coolest facts about high-interest topics, from prehistoric people to fashion, sports, outlaws, ghosts, weird plants, and more! The engaging, play-along format makes learning exciting!